2012
DOI: 10.1089/hum.2011.200
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-Associated Virus Serotype 9 Transduction in the Central Nervous System of Nonhuman Primates

Abstract: Widespread distribution of gene products at clinically relevant levels throughout the CNS has been challenging. Adeno-associated virus type 9 (AAV9) vector has been reported as a good candidate for intravascular gene delivery, but low levels of preexisting antibody titers against AAV in the blood abrogate cellular transduction within the CNS. In the present study we compared the effectiveness of vascular delivery and cerebrospinal fluid (CSF) delivery of AAV9 in transducing CNS tissue in nonhuman primates. Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
275
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(307 citation statements)
references
References 16 publications
28
275
4
Order By: Relevance
“…AAV vector administration. Despite being detectable, NAb titers in the CSF did not completely block AAV vector transduction in the brain, a result in contrast to previously published results (66) and in agreement with a recent study that explored CNS transduction following intra-CSF delivery in nonhuman primates with low serum NAb titers (64). Altogether, our study demonstrates that CNS gene transfer is possible in the presence of preexisting anticapsid antibodies.…”
Section: Figuresupporting
confidence: 88%
“…AAV vector administration. Despite being detectable, NAb titers in the CSF did not completely block AAV vector transduction in the brain, a result in contrast to previously published results (66) and in agreement with a recent study that explored CNS transduction following intra-CSF delivery in nonhuman primates with low serum NAb titers (64). Altogether, our study demonstrates that CNS gene transfer is possible in the presence of preexisting anticapsid antibodies.…”
Section: Figuresupporting
confidence: 88%
“…Evidence of effi cacy has also been demonstrated following CSF administration of AAV vectors (serotypes 1, 2, 5, and 9) in MPS 1, MPS III, and GM1-gangliosidosis mice ( 102,106,107 ). Importantly, the translatability of this route of delivery in the CNS of larger animals such as dogs and primates has been verifi ed ( 49,84,102 ). However, because the ependymal cell lining has a turnover rate of approximately 130 days ( 109 ) and because readministration of the identical AAV serotype vector is currently untenable, it is unclear whether this approach will provide long-term benefi ts.…”
Section: Effi Cacy Of Intracranial Delivery Of Aav Vectors For Neuropmentioning
confidence: 96%
“…An example of an AAV serotype vector that can reportedly cross the blood-brain barrier of mice and nonhuman primates is AAV9 ( 67,84 ). Indeed, systemically delivered recombinant AAV9-based vectors have been demonstrated to successfully treat the CNS disease in mouse models of the LSDs MPS IIIA ( 80 ) and MPS IIIB ( 85 ).…”
Section: Prospects Of Systemically Delivered Aav Vectors To Address Tmentioning
confidence: 99%
“…In 2009, Foust et al [21] reported that AAV serotype 9 (AAV9) vectors could cross the intact BBB in neonates and adult mice and yield "widespread" transgene expression in astrocytes, neurons, and endothelial cells. This was followed by reports showing that this finding translated to non-human primates (NHPs) [47,48] and could be achieved with other AAV serotypes [49]. The term "widespread" to describe the transduction pattern of intravenously injected AAV9 may be confusing to those not involved in the field.…”
Section: Virus-based Systemsmentioning
confidence: 99%
“…The field of CNS gene therapy is evolving rapidly with the discovery of new viral vectors, mainly AAV capsids, with remarkable CNS tropism after vascular [21,36,49,[96][97][98], and CSF administration [18,36,47]. A large range of AAV capsids has been investigated for their CNS gene transfer properties by direct intracranial injection [99][100][101][102].…”
Section: Challengesmentioning
confidence: 99%